Installation of central air conditioning system / Muhammad Zaieful Danial Mohd Zaidi - Mohd Zaidi, Muhammad Zaieful Danial (Universiti Teknologi MARA, Perak, 2019)
Central air conditioning system that also known as centralized air conditioning usually been used for the large a usually can been used for the large area to support in cooled the whole area. The central air conditioning system is one of the economical air conditioner system for the commercial buiding. The main objective of this research are to investigate the method or procedure used when install an air-conditioning system, to determine the problems occurred and solutions taken to solve the problems, to investigate the time needed to install an air-conditioning at Kuala Lumpur Health Clinic at Taman Tasik Titiwangsa, Kuala Lumpur.